Thermal Vacuum Teston the Precise Temperature Controlling Performance of Loop Heat Pipe - Zhao Shilei; Gao Teng; Yang Tao; Meng Qingliang (Zhileng xuebao)
An improved loop heat pipe (LHP) with high performance was developed in this paper. It has temperature controlling and heat-dissipating characteristics for multi-distributed heat sources by detaching the driving and dissipating power. To investigate the precise temperature controlling performance, the improved LHP was tested for the thermal control of four charge-coupled device (CCD) components on a camera in a vacuum chamber; stable operating tests, heat compensation power tests, and different powers on the evaporator tests were carried out. Test results showed that the improved LHP can control the temperature of the CCD in the range of ±0.5 oC by controlling the accumulator temperature. Three methods to maintain the CCD temperature stability were introduced for the temperature fluctuations caused by device switches and their feasibilities were verified through experimental and theoretical analysis.